1999
DOI: 10.1111/j.1471-0528.1999.tb08107.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective deficit of angiogenic growth factors characterises pregnancies complicated by pre‐eclampsia

Abstract: Objective To compare serum levels of angiogenic growth factors vascular endothelial growth factor (VEGF), placental growth factor (PlGF) and angiogenin in pre-eclamptic women and matched controls.Design Retrospective analysis of -70°C stored serum of women who developed pre-eclampsia and matched controls. Conclusions Decreased serum levels of VEGF and PlGF characterise, and therefore seem to be of importance during (the development of), pre-eclampsia. This selective deficit of angiogenic growth factors might i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(92 citation statements)
references
References 34 publications
4
84
1
3
Order By: Relevance
“…On the other hand, our results are contradictory to several studies [12][13][14], which demonstrated significant decrease of serum VEGF levels in preeclampsia. Levine et al [25] reported that the antiangiogenic protein, total soluble fms-like tyrosine kinase 1 (sFlt-1), is significantly elevated in serum of women with preeclampsia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, our results are contradictory to several studies [12][13][14], which demonstrated significant decrease of serum VEGF levels in preeclampsia. Levine et al [25] reported that the antiangiogenic protein, total soluble fms-like tyrosine kinase 1 (sFlt-1), is significantly elevated in serum of women with preeclampsia.…”
Section: Discussioncontrasting
confidence: 99%
“…Maternal and fetal circulating angiogenin levels did not differ significantly in pregnancies with small-for-gestational age and appropriate-forgestational age infants [17]. Only two studies have shown that serum angiogenin concentration did not change significantly in preeclampsia when compared to that of controls [13,18].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, although the properties of VEGF have rapidly led to its investigation as a potential pathophysiological molecule in preeclampsia, there has been considerable controversy over the levels of circulating VEGF during the last 10 years (Baker et al 1995;Bates et al 2006;Sharkey et al 1996). A large number of studies have shown that free available VEGF levels are significantly reduced in preeclampsia (Bates et al 2006;Livingston et al 2000;Reuvekamp et al 1999). Therefore, although the total levels of VEGF may be increased in this disorder, the physiologically active concentration may actually be reduced (Bates et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…# Corresponding author, E-mail: qiao_fuyuan@126.com growth factor (VEGF), which plays a critical role in the embryogenesis and the tumor angiogenesis, was found to express in both placenta tissue and blood serum of preeclampsia patients [4] . Recent studies showed that VEGF expression in preeclampsia pregnancies was abnormal [5,6] . On the basis of these pieces of evidence, we speculated that the endothelium damage in preeclampsia was associated with aberrant VEGF expression.…”
mentioning
confidence: 98%